Pharmacokinetics of marbofloxacin in pigs after intravenous and intramuscular administration of a single dose of 8 mg/kg: dose proportionality, influence of the age of the animals and urinary elimination - Schneider, M (J Vet Pharmacol Ther, 2014)
The pharmacokinetics of marbofloxacin in pigs were evaluated as a function of dose and animal age following intravenous and intramuscular administration of a 16% solution (Forcyl®). The absolute bioavailability of marbofloxacin as well as the dose proportionality was evaluated in 27-week-old fattening pigs. Blood PK and urinary excretion of marbofloxacin were evaluated after a single intramuscular dose of 8 mg/kg in 16-week-old male pigs. An additional group of 12-week-old weaned piglets was used for the evaluation of age-related kinetics. The plasma and urine concentration of marbofloxacin was determined using a HPLC method. Pharmacokinetic parameters were calculated using noncompartmental methods. After intravenous administration in 27-week-old fattening pigs, the total body clearance was 0.065 L/h·kg. After intramuscular administration to the same animals, the mean observed C(max) was 6.30 μg/mL, and the AUC(INF) was 115 μg·h/mL. The absolute bioavailability was 91.5%, and dose proportionality was shown within the dose range of 4–16 mg/kg. The renal clearance was about half of the value of the total clearance. The total systemic clearance values significantly decreased as a function of age, being 0.092 L/h·kg and 0.079 L/h·kg in pigs aged 12 and 16 weeks, respectively.